Alimentation élitaire dans la moyenne vallée de la Loire autour de l'an Mil - Gaëtan Jouanin; Aurélia Borvon; Chloé Genies; Anaïs Berrier (Revue Archéologique du Centre de la France)
Based on a zooarchaeological corpus from five high-status sites located in the middle Loire valley, this paper aims to confirm or relativise the criterious traditionally used to identify food habits of elites in the end of "premier Moyen Âge". Thus, first analysed elements are proportions and slaughter patterns of domestic triad (cattle, pig and caprines) as well as the part played by poultry and wild species in the meat diet. Associated with these quantitative criteria are qualitative criteria concerning faunal diversity, the presence of rare species (peacock, bear, sturgeon) and, to a lesser extent, the part played by aquatic ressources (fishes and molluscs).